Administration of nitrofurantoin in dogs with lower urinary tract infections: 14 cases (2013‐2019). (27th October 2020) - Leuin, A. S.; Hartmann, F.; Viviano, K.
Abstract : Objectives: The purpose of this study was to describe the clinical use of nitrofurantoin in client‐owned dogs with lower urinary tract infections. The primary aim was to describe the patient population, dosage, treatment duration, outcome and side effects. Materials and Methods: Medical records in an institution were retrospectively reviewed from July 2013 to January 2019. Results: Nitrofurantoin was prescribed in this clinical population of 14 client‐owned dogs for lower urinary tract infections. Recurrent urinary tract infection was the clinical diagnosis in all dogs. Each dog's urinary tract infection was associated with a nitrofurantoin‐susceptible, multidrug‐resistant uropathogen. The median dosage and duration of nitrofurantoin treatment was 4.3 mg/kg by mouth every 8 hours for 14 days. Twelve of the 14 dogs had successful outcomes including bacteriologic cure (n = 9), clinical cure (2) and resolution of target bacteria (1). Treatment failures (n = 2) were associated with uropathogens developing progressive nitrofurantoin resistance. Clinical Significance: In some dogs with recurrent lower urinary tract infections, nitrofurantoin may be an effective antibiotic for treatment of nitrofurantoin‐susceptible uropathogens. Treatment failures were associated with progressive uropathogen resistance. Urine bacterial culture and quantitative susceptibility testing are essential to initiating and monitoring treatment due to the multidrug‐resistant isolates and, in some cases, persistent bacteriuria in the face of treatment.